Innovative learning strategies in shaping noble character based on Islamic values - Shohifaha , Salsabila; Suharsono, Suharsono (At-Tajdid: Jurnal Ilmu Tarbiyah, 2025)
Education plays a crucial role in shaping students' noble character, especially in the context of Islamic education. Innovative learning strategies are essential for creating an effective and enjoyable learning environment while deeply instilling Islamic values. This study explores various innovative learning strategies that can be applied in the educational process to develop character and noble morals. The research employs a literature review method with a qualitative approach, referencing Islamic education theories and innovative learning models. The findings indicate that integrating technology into Islamic education enhances students' understanding and internalization of noble character values. Additionally, the role of teachers as facilitators, motivators, and role models is pivotal to the success of value-based learning. With the appropriate strategy implementation, education not only produces intellectually capable individuals but also fosters noble character in line with Islamic teachings.